2022
DOI: 10.3390/diagnostics12051180
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Monitoring of Corneal Dendritic Cells in the Subbasal Nerve Plexus during Trastuzumab and Paclitaxel Breast Cancer Therapy—A One-Year Follow-Up

Abstract: Paclitaxel and trastuzumab have been associated with adverse effects including chemotherapy-induced peripheral neuropathy (CIPN) or ocular complications. In vivo confocal laser scanning microscopy (CLSM) of the cornea could be suitable for assessing side effects since the cornea is susceptible to, i.e., neurotoxic stimuli. The study represents a one-year follow-up of a breast cancer patient including large-area in vivo CLSM of the subbasal nerve plexus (SNP), nerve function testing, and questionnaires during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Corneal dendritic cell density increased dramatically without corneal nerve alterations in a patient with breast cancer after 11 weeks of treatment with paclitaxel and trastuzumab 52 and then returned to baseline values after cessation of paclitaxel therapy. 53 In the present study, baseline NCF and NCP were higher in patients who switched disease-modifying treatment during follow-up and baseline NCP was higher in patients on interferon. In this context, we hypothesize that higher corneal IC density may reflect reduced treatment effectiveness against underlying inflammation.…”
Section: Discussionsupporting
confidence: 46%
“…Corneal dendritic cell density increased dramatically without corneal nerve alterations in a patient with breast cancer after 11 weeks of treatment with paclitaxel and trastuzumab 52 and then returned to baseline values after cessation of paclitaxel therapy. 53 In the present study, baseline NCF and NCP were higher in patients who switched disease-modifying treatment during follow-up and baseline NCP was higher in patients on interferon. In this context, we hypothesize that higher corneal IC density may reflect reduced treatment effectiveness against underlying inflammation.…”
Section: Discussionsupporting
confidence: 46%
“…The experimental data confirmed that in vivo confocal microscopy is a helpful, non-invasive tool with promise for the diagnosis of CIPN [20]. However, at the present time, despite a case report [21], no prospective longitudinal studies which monitor breast cancer patients before, during, and after the course of chemotherapy exist for detecting corneal nerves by using advanced biophotonic techniques. In addition, currently, representative selections of CLSM images and valid image analyses are a challenge.…”
Section: Introductionmentioning
confidence: 57%
“…The most commonly used methodology in clinical research settings involves random selection of a set number of images with sufficient quality from a pool of images obtained from a participant's eye prior to analysis 33,34 . Sampling strategy of adequate images has been shown to produce sufficient accuracy, however for longitudinal or clinical monitoring purposes, real-time widefield imaging capabilities may provide more insight into regional changes in the cornea over time or following exposure to various stimuli 77,78 . In fact, a minimum repeatable area of 1.5 mm 2 is shown to have reliable morphological characterisation of the sub-basal nerve plexus 79,80 .…”
mentioning
confidence: 99%